The influence of the Wesleyan Methodist missions in Southern Rhodesia, 1891-1923 - Zvobgo, C. J. M. (Christianity south of the Zambezi, 1973)
Anfangsschwierigkeiten und Einflüsse der Methodisten-Kirche